Perceptions of postgraduate students on the relationship between thesis development and performance of a supervisor - Bayona Ore, Sussy (Journal of Turkish Science Education, 2021)
Although thesis supervision has been widely studied, little is known about supervisors’ performance dimensions and thesis development from a quantitative perspective. For this reason, this research aims to analyse the relationship between thesis development and supervisors’ performances according to the perceptions of postgraduate students. A quantitative research methodology and a Spearman’s rank correlation was used. A survey was administered to 51 postgraduate students from a public university. The results indicated a significant correlation between thesis development and supervisor performance dimensions such as skills, roles, and personal qualities. The academic capacity, knowledge, research experience of supervisor is significant and the supervisors understand the regulations and rules of the supervision process. The supervisors must have knowledge of supervision styles and apply it taking into account the characteristics of the students. A framework of procedures and guidelines for postgraduate supervision must be established to improve the supervision process.
Keywords: Supervisor performance; cognitive skills; personal qualities; role function; thesis